(untitled) (PerCursos, 2021)
Understanding the transformations that society has been going through in the last decades is crucial in order to understand the historical relationship between State and Market. In the meantime, public utilities are the focus that unites and, at the same time, separates them. The objective of this text is to highlight the differences between the gradual transfer of essential public services to the private sector as part of the neoliberal process that began in Europe in the late 1970s and has been advocated in slower stages in Brazil. Analyzing the convergences between what happened there, including with multiple concepts, and what happens in the national territory mainly after 2016, understand a process that has its own particularities and historical determinations in each geographic context, despite presenting some historical and interrelated assumptions. In this sense, to implement a minimal State in a country characterized by incomplete citizenship processes and the most diverse inequalities, incurs in extending the withdrawal of scarce rights and greatly contributes to social injustice and the misery of a significant portion of Brazilian society. The research procedure – bibliographical – is both analytical and comparative, based on literature from the European context (Services of General Economic Interest – SGEI) to investigate the process undertaken here.